2017
DOI: 10.1186/s12877-017-0642-x
|View full text |Cite
|
Sign up to set email alerts
|

Implementation and effects of Movement-oriented Restorative Care in a nursing home – a quasi-experimental study

Abstract: BackgroundThe prevalence of dementia is expected to increase rapidly, and institutionalization is a common consequence of the disease. Dependence in activities of daily living (ADL) is a predictor for institutionalization and a determinant for the quality of life (QoL). A promising method to increase functional independence in nursing homes is a restorative care or function focused care (FFC) approach. Movement-oriented restorative care (MRC) is derived from the concept of FFC and restorative care and focuses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(58 citation statements)
references
References 37 publications
0
58
0
Order By: Relevance
“…Table 1 displays characteristics of included studies. Most of the studies were from the Netherlands [19,21,29,30,37,42] and the UK [23,25,28,32,33,40] (each n = 6), followed by Australia [24,34,41], Canada [20,22,27], Norway [26,31,36] (each n = 3), Germany [38,39], and Belgium [18,43] (each n = 2). One multinational study took place in Italy and the Netherlands [35].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Table 1 displays characteristics of included studies. Most of the studies were from the Netherlands [19,21,29,30,37,42] and the UK [23,25,28,32,33,40] (each n = 6), followed by Australia [24,34,41], Canada [20,22,27], Norway [26,31,36] (each n = 3), Germany [38,39], and Belgium [18,43] (each n = 2). One multinational study took place in Italy and the Netherlands [35].…”
Section: Resultsmentioning
confidence: 99%
“…In the studies they analysed, poor health status and cognitive impairment were reported only once. In our review, factors directly relating to characteristics of the person with dementia were described in more than one quarter of included studies [20,21,26,29,30,35,43]. Publications with other patient groups also reported on patient-or resident-related influencing factors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…See Table S1. Thirteen studies had a total quality score between 60% and 86% (Galik et al, 2008; Guidetti & Ytterberg, 2011; Hafsteinsdóttir, Algra, Kappelle, & Grypdonck, 2005; Hedman, Eriksson, von Koch, & Guidetti, 2019; Henskens, Nauta, Drost, & Scherder, 2018; Henskens, Nauta, Scherder, Oosterveld, & Vrijkotte, 2017; Henskens, Nauta, van Eekeren, & Scherder, 2018; Kerse et al, 2008; Parsons, Sheridan, Rouse, Robinson, & Connolly, 2013; Peri et al, 2008; Resnick et al, 2006; Resnick, Galik, Gruber‐Baldini, & Zimmerman, 2009; Tuntland, Aaslund, Espehaug, Førland, & Kjeken, 2015), and seven studies had a quality score between 40% and 59% (Bertilsson et al, 2014; Galik, Resnick, Hammersla, & Brightwater, 2013; Galik, Resnick, Lerner, Hammersla, & Gruber‐Baldini, 2015; Resnick, Gruber‐Baldini, et al, 2009; Resnick, Galik, Gruber‐Baldini, & Zimmerman, 2011; Sidani, Streiner, & LeClerc, 2012; Tinetti et al, 2002). Four studies fulfilled less than 40% of the quality criteria and were excluded from the review (Engelman, Mathews, & Altus, 2002; Johnson et al, 2004; Lim, 2003; Padula, Hughes, & Baumhover, 2009).…”
Section: Resultsmentioning
confidence: 99%